2017
DOI: 10.3238/arztebl.2017.0673
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Treatment of Homeless People

Abstract: More heath care resources need to be made available to the homeless beyond standard medical care. Concrete suggestions are discussed in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
0
27
0
21
Order By: Relevance
“…In addition, structural and administrative barriers that homeless people experience, such as lack of health coverage, limited access to and provision of both preventive and treatment services for dental and overall health conditions [15-19, 25, 27], should be eliminated to reduce the premature morbimortality of this population. Furthermore, to reduce experiences of discrimination and stigma, it is essential that health care professionals, including dentists, [16,17] receive training on serving homeless people in their settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, structural and administrative barriers that homeless people experience, such as lack of health coverage, limited access to and provision of both preventive and treatment services for dental and overall health conditions [15-19, 25, 27], should be eliminated to reduce the premature morbimortality of this population. Furthermore, to reduce experiences of discrimination and stigma, it is essential that health care professionals, including dentists, [16,17] receive training on serving homeless people in their settings.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are homeless (those without a fixed, regular, and adequate night-time residence) had higher mortality rates and experience the dual burdens of DPs, CDs compared to the general population [4,5,14] due to structural and system-level barriers (e.g., lack of affordable housing, shrinking safety nets, health care systems models, health services affordability, lack of accessibility to health and social services) [15][16][17][18][19], social exclusion [18]. People experiencing homelessness frequently suffer serious mental disorders (e.g., psychotic disorders, mood and personality disorders, substance and alcohol use disorders) [20,21] and modifiable risk factors (e.g., diet, smoking) [22,23], which also contribute to poor health profiles and premature mortality [5,21].…”
Section: Introductionmentioning
confidence: 99%
“…(33,34,(46)(47)(48)51,(55)(56)(57) Flexible healthcare delivery CMOC 6 ( g 8) explores the context of exibility in healthcare services delivery in terms of appointment length, availability of walk-in appointments and selfreferral, opportunistic add-on services such as vaccinations and screenings, allowing dogs, trauma-informed practice and understanding of behaviours that trauma can result in, and more. (21,26,37,40,46,47,50,51,55,(64)(65)(66)(67) In this context, providers and staff with expertise and experience with the population group are able to anticipate the common interventions that may be needed, to adapt to the particular needs of the patient in front of them, and to provide the treatment that is most needed in the current situation. Communication is tailored to the patient with awareness of potential literacy issues common in the population.…”
Section: Resourcingmentioning
confidence: 99%
“…Lee et al [ 15 ] found that, in North America, hypertension, high cholesterol, and diabetes were not more prevalent in the homeless than in the general population but were often poorly controlled. It was not easy to control hypertension, hyperlipidemia, and hyperglycemia for the homeless [ 16 ]. The prevalence of CVD risk for the homeless is often different in different regions, races, and countries.…”
Section: Introductionmentioning
confidence: 99%